Electrochemical rehabilitation methods for reinforced concrete structures : a state of the art report - Mietz, J. (Publications (European Federation of Corrosion) ;, 1998)
This is a state of the art report on two of the main electrochemical methods for the rehabilitation of reinforced concrete structures - electrochemical chloride extraction and electrochemical realkalisation. The principles, laboratory and field experience, effectiveness and long-term behaviour of the procedures are considered.